CD133 Promotes Adhesion to the Ovarian Cancer Metastatic Niche. (7th April 2018) - Roy, Lynn; Bobbs, Alexander; Sattler, Rachel; Kurkewich, Jeffrey L; Dausinas, Paige B; Nallathamby, Prakash; Cowden Dahl, Karen D
Cancer stem cells (CSCs) are an attractive therapeutic target due to their predicted role in both metastasis and chemoresistance. One of the most commonly agreed on markers for ovarian CSCs is the cell surface protein CD133. CD133+ ovarian CSCs have increased tumorigenicity, resistance to chemotherapy, and increased metastasis. Therefore, we were interested in defining how CD133 is regulated and whether it has a role in tumor metastasis. Previously we found that overexpression of the transcription factor, ARID3B, increased the expression of PROM1 (CD133 gene) in ovarian cancer cells in vitro and in xenograft tumors. We report that ARID3B directly regulates PROM1 expression. Importantly, in a xenograft mouse model of ovarian cancer, knockdown of PROM1 in cells expressing exogenous ARID3B resulted in increased survival time compared with cells expressing ARID3B and a control short hairpin RNA. This indicated that ARID3B regulation of PROM1 is critical for tumor growth. Moreover, we hypothesized that CD133 may affect metastatic spread. Given that the peritoneal mesothelium is a major site of ovarian cancer metastasis, we explored the role of PROM1 in mesothelial attachment. PROM1 expression increased adhesion to mesothelium in vitro and ex vivo. Collectively, our work demonstrates that ARID3B regulates PROM1 adhesion to the ovarian cancer metastatic niche.